Hukuman Pidana Mati dalam KUHP Baru dan Perspektif Abolisionalis serta Retensionis - Dita Melati Putri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
In Law Number 1 of 2023 or the New Criminal Code, the death penalty is regulated as an extreme punishment for serious crimes with a stricter approach. Article 67 of the New Criminal Code states that the death penalty is no longer the main punishment, but the last alternative after a ten-year probation period. This study uses a normative method with two categories of legal sources: primary legal materials, namely laws that regulate the death penalty, and secondary legal materials, which explain and interpret primary laws. The debate on the death penalty involves two main currents of thought: retensionists, who favor the application to serious crimes, and abolitionists, who reject it because of human rights concerns and the risk of judicial wrongdoing. Criticism of the death penalty includes the issue of the right to life and its effectiveness in reducing crime rates, especially in corruption and narcotics cases. In this study, it was found that the New Criminal Code tries to balance the retributive and rehabilitative aspects by providing an opportunity for remorse before the application of the penalty, describing Indonesia's legal efforts to maintain the death penalty with a more selective and strict application.